Application of Virtual Reality in the Treatment of Claustrophobia in Adolescents - Iparraguirre-Villanueva, Orlando (2023)
Claustrophobia is an anxiety disorder that requires the priority of the medical profession. The causes of claustrophobia are not fully understood, but it is believed that there may be a genetic factor. People suffering from this disorder may experience physical and emotional symptoms such as sweating, dizziness, panic, and shortness of breath when in enclosed spaces. The aim of this work is to develop a Virtual Reality (VR) application for the treatment of claustrophobia. The Extreme Programming Methodology (XP) and the Unity graphics engine were used to develop the application. To validate the experiment, we worked with a sample of 50 students with an average age of 15 years. The findings showed that the VR application did not significantly increase the Beats Per Minute (BPM) of the participants, who all registered between 60 and 100 BPM. However, it did manage to increase the feeling of realism when wearing the VR goggles. In conclusion, the application of VR as a tool to treat claustrophobia allowed the recreation of realistic claustrophobic scenarios in which participants were tested to assess their behavior and cardiac BPM.